ASSESSING THE ROLE OF SCHOOL AND FAMILY ENVIRONMENT ON STUDENTS' LEARNING MOTIVATION: CASE STUDY AT PUBLIC VOCATIONAL SCHOOL - Handayani, Wening; Wahono, Puji; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this assessment is to determine the impact of family and school environments on students' learning motivation at SMKN 51 Jakarta. This study uses a descriptive correlation research design. A sample of 152 students from Public Vocational High School 51 Jakarta was obtained through proportional random sampling techniques. By distributing questionnaires using a Likert scale. The data analysis technique used multiple linear regression using SPSS (Statistical Product for Service Solutions) as a tool. The results of the study indicate that, (1) there is a simultaneous influence between the School Environment and Family Environment on Learning Motivation, (2) there is a positive and significant influence of the School Environment on Learning Motivation, and (3) there is a positive and significant influence of the Family Environment on Learning Motivation. The study highlights the importance of collaborative support for a conducive school and family environment to increase students' learning motivation.